Does Change in ESR and CRP Guide the Timing of Two-stage Arthroplasty Reimplantation?. Issue 2 (February 2019) - Stambough, Jeffrey B.; Curtin, Brian M.; Odum, Susan M.; Cross, Michael B.; Martin, J. Ryan; Fehring, Thomas K.
Abstract: Background: Two-stage reimplantation arthroplasty is a commonly used approach for treating chronic periprosthetic joint infections. A prereimplantation threshold value of erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) to determine infection eradication and the proper timing of reimplantation remains ill defined. We theorized that rather than a specific numeric threshold, a percentage of improvement in these serology markers might improve diagnostic accuracy in determining the timing of reimplantation. Question/purposes: We investigated if (1) the percent, or delta, change in ESR and CRP values from preresection to prereimplantation ([INCREMENT]ESR, [INCREMENT]CRP) is a useful marker of infection eradication and (2) whether the initial PJI causative organism (resistant, nonresistant, or culture-negative) is associated with serum ESR and CRP values before and after treatment with an antibiotic spacer and parenteral antibiotic therapy. Methods: We retrospectively reviewed 300 patients, nine of whom were lost to followup, treated with a two-stage revision THA or TKA protocol between 2005 and 2014 from two separate institutional arthroplasty registries. Serum ESR and CRP values were recorded at two designated points: (1) preresection and (2) after 6 weeks of intravenous antibiotic therapy with a drug-eluting spacer and completion of an organism-specific intravenous antibiotic regimen. Patient records were reviewed electronically for causative species of infection, revision surgeries, and recurrent/persistent infection based on Musculoskeletal Infection Society criteria for a minimum of 2 years. Forty-eight of 291 patients (16%) underwent a revision procedure for recurrent or persistent infection, whereas 31 patients (10%) were revised for noninfectious reasons. The [INCREMENT]ESR, [INCREMENT]CRP, culture results, and patient demographics were recorded and analyzed with receiver operator curves controlling for American Society of Anesthesiologists (ASA) class. Results: Receiver operator characteristic area under the curves (AUC) demonstrated that both the [INCREMENT]ESR (AUC = 0.581) and [INCREMENT]CRP (AUC = 0.539) percentages were poor markers of recurrent or persistent infection. When comparing preresection with prereimplantation values, the median percent [INCREMENT]ESR was 50% (interquartile range [IQR], 17%-77%) for those patients who remained infection-free versus 59% (IQR, 29%-78%) for those who developed reinfection (p = 0.540). The median percent [INCREMENT]CRP was 77% (IQR, 47%-92%) for those patients who remained infection-free versus 79% (IQR, 46%-95%) for those who experienced reinfection (p = 0.634). Although no significant differences were found between organism type and CRP values at the two time points, the preresection ESR level was higher in patients infected with resistant bacteria (median, 69; IQR, 60%-85%) compared with nonresistant organisms (median, 55; IQR, 33%-83%; p = 0.020). Conclusions: The percent change in serum ESR and CRP inflammatory markers before and after two-stage reimplantation for PJI was not associated with reinfection risk when controlling for ASA class. Although a return to normal serology infrequently occurs before reimplantation, [INCREMENT]ESR and [INCREMENT]CRP provide no additional diagnostic accuracy to determine the timing of reimplantation. Furthermore, the pre- and postresection serology values have no meaningful relationship to resistant or nonresistant pathogens. Decisions for reimplantation must take into account multiple variables rather than a specific threshold change in serum inflammatory markers. Level of Evidence: Level III, diagnostic study.